Where to Go with Corporate Sustainability? Opening Paths for Sustainable Businesses through the Collaboration between Universities, Governments, and Organizations - Vieira Nunhes, Thais [UNESP]; Viviani Garcia, Enzo [UNESP]; Espuny, Maximilian [UNESP]; Homem de Mello Santos, Vitor [UNESP]; Isaksson, Raine; Jose de Oliveira, Otavio [UNESP] (Mdpi, 2021)
This study aims to identify and analyze the Scientific-Technical Scenario on Corporate Sustainability (STS-CS) and propose a Triple Helix-based framework for its development and guidance of future scientific and technological investments. The study was developed using a combined method of bibliometric analysis and content analysis of scientific papers and technical publications (patents, white papers, publications from public bodies, etc.). The scientific papers were searched in the Scopus database and technical publications in the Orbit Intelligence, ProQuest, and UN Global Compact platforms. The STS-CS was analyzed in light of the scientific and technical literature and experience of the authors of the study, which allowed the proposition of the framework with initiatives expanded and adapted to the domains of the Triple Helix sectors Universities, Governments, and Organizations through a process of enriching the good practices identified in the CS scenarios. The main academic contribution of this work is the upgrade of the scientific block of knowledge on CS based on cooperation between the sectors of Triple Helix that expands and deepens the research aimed at contributing to sustainable business development. As for the applied contributions, companies can identify business opportunities to increase their profits in a sustainable way, governments can find suggestions for public measures for the development of CS, and universities can identify recommendations for training professionals capable of managing socio-economic issues and developing partnerships with companies for the innovation and development of sustainable products and processes.
Keywords: corporate sustainability; sustainable management; framework; CSR; sustainable development